Hypohemo in superficial lymphangioma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Lymphangioma (L) is a localized malformation of lymphatic vessels, not connected with normal lymphatic circulation. L can be superficial, consisting of cystic cavities of 1-3 mm in diameter, with serous or serum-hematic content and deep, consisting of larger and deeper cavities. By hypopopion we mean the presence of pus in the anterior chamber of the eyeball; the pus, which is located between the cornea anteriorly and the iris and the crystalline posteriorly with the sclero-corneal limbus laterally, assumes the appearance of a yellowish semicircle with rectilinear upper margin. This phenomenon is due to the presence of heavy corpuscular pus at the bottom while the lighter water mood remains at the top. The same phenomenon occurs in pustules, especially in plantar ones with a thicker roof, where the underlying pus separates from the overlying plasma. In the case of the hypohemo, the heavier red blood cells remain in the bottom.